2019
DOI: 10.1002/adma.201905975
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chiral, Helical Nanoparticle Superstructures: Progress and Prospects

Abstract: Chiral objects are defined as nonsuperimposable conformations that are mirror images of each other, much like a pair of left and right hands. In fact, the word "chiral" derives from the Greek word "χειρ" (kheir), which translates to "hand." Most biomolecules exist in only one particular conformation. For example, amino acids within large protein and peptide molecules are exclusively in the l-form (left-handed). It has long been considered that the phenomenon of homochirality (predominant occurrence of one conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 77 publications
1
82
0
1
Order By: Relevance
“…A primary driving force behind this development is the breakthrough in design and fabrication of artificial metallic nanostructures, ranging from top-down techniques such as focused ion beam milling, [40] electron-beam lithography [41] and direct laser writing, [42] to bottom-up methods like chemical synthesis and self-assembly. [39,43] Together with theories that can elegantly describe the interaction between chiral molecules and plasmonic nanostructures, [44][45][46][47] the study of chirality has entered a fast development path. There have been several reviews focusing on various aspects of this field, including fabrication, [39,43,48,49] theories, [50][51][52] and applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary driving force behind this development is the breakthrough in design and fabrication of artificial metallic nanostructures, ranging from top-down techniques such as focused ion beam milling, [40] electron-beam lithography [41] and direct laser writing, [42] to bottom-up methods like chemical synthesis and self-assembly. [39,43] Together with theories that can elegantly describe the interaction between chiral molecules and plasmonic nanostructures, [44][45][46][47] the study of chirality has entered a fast development path. There have been several reviews focusing on various aspects of this field, including fabrication, [39,43,48,49] theories, [50][51][52] and applications.…”
Section: Introductionmentioning
confidence: 99%
“…[39,43] Together with theories that can elegantly describe the interaction between chiral molecules and plasmonic nanostructures, [44][45][46][47] the study of chirality has entered a fast development path. There have been several reviews focusing on various aspects of this field, including fabrication, [39,43,48,49] theories, [50][51][52] and applications. [38,53,54] The goal of the present review, as illustrated in Scheme 1, is to elaborate the three physiochemical mechanisms of chirality transfer from sub-nanometer biochemical molecules to submicrometer metallic nanostructures, namely electromagnetic interaction induced chirality transfer, chiral assembly and chirality inheritance, molecular conformation change induced chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the extraordinary CD responses of plasmonic chiral nanostructures have gained considerable attention, where the excitation of localized surface plasmon resonances (LSPRs) significantly enhances the light-structure interaction strength due to their extremely large dipole moments, and the generated CD signals are thus orders of magnitude larger than that of natural compounds [9][10][11][12][13][14][15][16][17]. Such enhanced plasmonic chirality is also featured with flexible modulation of both CD resonance magnitude and frequency through manipulating the structural geometry and constituents [4,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of chirality to TMOs has revolutionized the motif of TMOs with respect to their applications in area of chiroptical sensing and detection, enantioselective catalysis, biological‐tissue‐based therapy, and chirality‐based devices. Since a body of related reviews has well summarized the details about the possible applications of chiral inorganic NCs, [ 6,47–55 ] we would prefer only to highlight some representative examples of chiral TMOs here: 1)Chiroptical sensing and detection: Xu and co‐workers [ 56 ] reported recently that chiral CuxOS@ZIF‐8 nanostructures can be used as ultrasensitive probe for detection of H 2 S in vivo with the limit of detection of 0.3 × 10 −9 and 2.2 × 10 −9 m for CD and fluorescence methods because H 2 S can reduce the chiroptical intensity and increase the fluorescent signal of the nanostructures ( Figure A). Jiang's group [ 57 ] also demonstrated that cysteine‐capped Au/Fe 3 O 4 NPs can enantioselectively detect the percentage of d ‐tyrosine in a mixture of enantiomers via cysteine as the chiral selector. 2)Enantioselective catalysis: Qu and co‐workers [ 58 ] developed phenylalanine‐modified cerium oxide nanoparticles (CeNPs) as chiral nanozyme for stereoselective oxidation of 3,4‐dihydroxyphenylalanine (DOPA) enantiomers where l ‐CeNP showed higher catalytic ability for oxidation of d ‐DOPA while d ‐CeNP were more effective to l ‐DOPA (Figure 4B).…”
Section: Applications and Perspectivesmentioning
confidence: 99%